Modelling Methane Hydrate Saturation in Pores: Capillary Inhibition Effects - Maria De La Fuente; Jean Vaunat; Héctor Marín-Moreno (Energies, 2021)
Experimental and field observations evidence the effects of capillarity in narrow pores on inhibiting the thermodynamic stability of gas hydrates and controlling their saturation. Thus, precise estimates of the gas hydrate global inventory require models that accurately describe gas hydrate stability in sediments. Here, an equilibrium model for hydrate formation in sediments that accounts for capillary inhibition effects is developed and validated against experimental data. Analogous to water freezing in pores, the model assumes that hydrate formation is controlled by the sediment pore size distribution and the balance of capillary forces at the hydrate–liquid interface. To build the formulation, we first derive the Clausius–Clapeyron equation for the thermodynamic equilibrium of methane and water chemical potentials. Then, this equation is combined with the van Genuchten’s capillary pressure to relate the thermodynamic properties of the system to the sediment pore size distribution and hydrate saturation. The model examines the influence of the sediment pore size distribution on hydrate saturation through the simulation of hydrate formation in sand, silt, and clays, under equilibrium conditions and without mass transfer limitations. The results show that at pressure–temperature conditions typically found in the seabed, capillary effects in very fine-grained clays can limit the maximum hydrate saturation below 20% of the host sediment porosity.